Cybersecurity awareness mobile apps for secondary school students: letsecure - Jafri, Azma Melia; Jamaluddin, Nur' Ain Zulaikha; Zulkifli, Zahidah (Kulliyyah of Information and Communcation Technology, IIUM, 2021)
As our world is connected through information technology, home internet users, including school students, are threatened by cyber-attacks. It leads to an increase in cybersecurity issues and cases. This proves that cybersecurity is receiving insufficient awareness. The most worrying part is when the pandemic Covid-19 outbreak occurred, more people spent their time working from home using the internet and spending their time by browsing the internet. The concern is more to those who are not aware of how bad and dangerous cybersecurity threats could happen to them. The objective of this paper is to study the current problem and awareness on cybersecurity of secondary school students that focuses on form 4 and 5 students in Malaysia. As part of the results, LetSecure is developed, which is a mobile application that can help to spread awareness about cybersecurity and cybersecurity as a career. In order to develop this system, surveys and interviews have been conducted. The data for surveys that have been collected are from secondary school students and interviews with counselors of SMK Sungai Pusu. The methodology that is being used for this application is System Development Life Cycle (SDLC) and the Object Oriented. LetSecure is developed focusing on the beginners level, which are secondary students and also for people who do not have any basics on cybersecurity or advanced technology. As a conclusion, this application will give benefits to secondary school students in terms of increasing their awareness on cybersecurity and to choose cybersecurity as a career for their future